Consumer response to corporate irresponsible behavior: Moral emotions and virtues - Grappi, Silvia; Romani, Simona; Bagozzi, Richard P. (Journal of business research, 2013)
A unique theoretical framework for explaining consumer word of mouth and protest behaviors against corporate irresponsibility is developed and tested. Through field surveys with adult consumers, this study demonstrates how consumers' negative moral emotional responses to corporate infractions instigate, in combination with other-regarding virtues, negative word of mouth and protest toward the corporation. Negative moral emotions include contempt, anger, and disgust; whereas other-regarding virtues entail justice, beneficence, equality, and communal cooperation. The results provide scholars and managers with means of improving their understanding and handling of consumers' reactions to corporate irresponsibility.